Pemanfaatan Smartphone Based Colorimetry Dalam Pengukuran Degradasi Metilen Biru Dengan Fotokatalitik CaO - Rahman, Kamaulana Adi; Alimuddin, Alimuddin; Hiyahara, Irfan Ashari (PROSIDING SEMINAR KIMIA, 2025)
Water pollution caused by textile industry waste, especially methylene blue, is a problem for the environment that needs to be addressed. Photocatalysis using calcium oxide (CaO) is one of the effective and environmentally friendly methods in degrading methylene blue. This study aims to determine the effect of CaO catalyst mass and pH on the rate of methylene blue degradation using smartphone-based colorimetry. This study was conducted by varying the mass of CaO 12.5 mg, 25 mg, 37.5 mg and 50 mg and pH variations of 7, 8, 9, and 10 in a 10 mg/L methylene blue solution. Degradation was carried out with visible light from a 100 W incandescent lamp. The concentration of methylene blue was measured using smartphone-based colorimetry. The results showed that contact time and CaO mass had a significant effect on the rate of methylene blue degradation. The optimum mass of photocatalysis was 50 mg and the optimum pH was 7. Keywords : Methylene Blue, CaO, Photocatalysis, Smartphone-based colorimetry